2022
DOI: 10.1038/s41598-022-07511-x
|View full text |Cite
|
Sign up to set email alerts
|

Neural oscillations during motor imagery of complex gait: an HdEEG study

Abstract: The aim of this study was to investigate differences between usual and complex gait motor imagery (MI) task in healthy subjects using high-density electroencephalography (hdEEG) with a MI protocol. We characterized the spatial distribution of α- and β-bands oscillations extracted from hdEEG signals recorded during MI of usual walking (UW) and walking by avoiding an obstacle (Dual-Task, DT). We applied a source localization algorithm to brain regions selected from a large cortical-subcortical network, and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 84 publications
1
13
0
Order By: Relevance
“…Regarding the first point, a substantial body of research consistently highlights modulations in alpha and beta bands, often manifested by an event-related desynchronization or a power decrease in sensorimotor regions, accompanied by a concurrent increase in ipsilateral areas, particularly parieto-occipital regions (Brinkman et al, 2014; de Lange et al, 2008; Di Nota et al, 2017; McFarland et al, 2000; Pfurtscheller, 2000; Pfurtscheller & Neuper, 1997; Pfurtscheller at al., 1997; Putzolu et al, 2022). However, our findings point out a significant interindividual variability (Höller et al, 2013; Wriessnegger et al, 2020), demonstrating the diverse brain responses observed among our participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the first point, a substantial body of research consistently highlights modulations in alpha and beta bands, often manifested by an event-related desynchronization or a power decrease in sensorimotor regions, accompanied by a concurrent increase in ipsilateral areas, particularly parieto-occipital regions (Brinkman et al, 2014; de Lange et al, 2008; Di Nota et al, 2017; McFarland et al, 2000; Pfurtscheller, 2000; Pfurtscheller & Neuper, 1997; Pfurtscheller at al., 1997; Putzolu et al, 2022). However, our findings point out a significant interindividual variability (Höller et al, 2013; Wriessnegger et al, 2020), demonstrating the diverse brain responses observed among our participants.…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, EEG recording, particularly the examination of the alpha (8–12 Hz) and beta bands (13–20 Hz), has also emerged as a valuable method for probing cerebral functioning with an excellent temporal resolution, in both motor and cognitive processes. Some researchers have indicated that MI increased brain activity in contralateral sensorimotor or posterior areas, often characterized by a power decrease or an event-related desynchronization in alpha and beta bands (Brinkman et al, 2014; de Lange et al, 2008; Di Nota et al, 2017; McFarland et al, 2000; Pfurtscheller, 2000; Pfurtscheller & Neuper, 1997; Pfurtscheller et al, 1997; Putzolu et al, 2022). However, other researchers have suggested opposite outcomes in the same areas with a power increase or event-related synchronization (Jacquet et al, 2021; Marks & Isaac, 1995; Neuper et al, 2006) or no modulations at all (Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The data analyzed in this paper have been collected from 19 healthy adults, as described in a recent publication from our group 24 . We excluded from participation subjects (i) with previous experience with MI techniques or training, (ii) with a history of neurological diseases, or (iii) being treated with any medication that affected the central nervous system.…”
Section: Methodsmentioning
confidence: 99%
“…At last, we created the leadfield matrix that expresses the scalp potentials corresponding to each source configuration. More details about head modeling have been previously reported 24 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation